The Spread of Vouchers among French Local Government: When Private Companies Reshape the Meaning of a Tool - Arnaud Lacheret (International Review of Public Policy)
Vouchers as tools of provision of social and individual subsidies are rather marked politically as they have been promoted by economists such as Milton Friedman and Friedrich Hayek. Despite their controversial political sense, vouchers have spread widely in the 2000 among the French local governments to provide individual subsidy. While in the USA the debate is strong between supporters and opponents of voucher systems, in France, the apparent neutrality of vouchers permitted them to spread at a local and regional scale without particular political tension. Our research, based on 45 qualitative interviews and on a wide source research within the local governments and private actors, showed that this silent spread is mainly due to the marketing and lobbying action of voucher companies that have done a lot to neutralize the vouchers and avoid all political debate on its their strong liberal roots.